UPAYA PENINGKATAN KUALITAS FRONT OFFICE DALAM MENINGKATKAN PELAYANAN PRIMA (SERVICE EXCELLENCE) DI THE 1O1 YOGYAKARTA - Martanto, Eko; Fatimah, Siti; Budi Setyawan, Erwin; Yuni Astuti, Andri; Khailut, M; Eka Sakti, Fahrizza; Mawarti Muji Astuti, Rina (PRIMA EKONOMIKA, 2026)
Abstract This study aims to analyze efforts to improve front office quality. In order to realize service excellence at THE 1O1 Yogyakarta Tugu, the front office, as the front line of hotel service, plays a crucial role in creating a positive impression. First And satisfaction visitor. The method that used in study This is qualitative descriptive with technique collection data through observation, interview, And studies Documentation. The results of the study indicate that efforts to improve front office quality are carried out through regular training, improving human resource competencies, implementing consistent standard operating procedures (SOP), and utilizing information technology to support services. Obstacles encountered include high employee turnover and differing guest expectations. However, these efforts have been able to make a positive contribution to improving guest satisfaction and hotel image. Thus, improving front office quality has proven to play a significant role in achieving excellent service in the hotel environment. Say key : front office, quality service, service excellent, service excellence, hotel.